The performance of African protected areas for lions and their prey. (May 2017) - Lindsey, P.A.; Petracca, L.S.; Funston, P.J.; Bauer, H.; Dickman, A.; Everatt, K.; Flyman, M.; Henschel, P.; Hinks, A.E.; Kasiki, S.; Loveridge, A.; Macdonald, D.W.; et al.
Abstract: Using surveys of experts associated with 186 sites across 24 countries, we assessed the effectiveness of African protected areas (PAs) at conserving lions and their prey, identified factors that influence conservation effectiveness, and identified patterns in the severity of various threats. Less than one third of sampled PAs conserve lions at ≥ 50% of their estimated carrying capacity (K), and less than half conserve lion prey species at ≥ 50% of K. Given adequate management, PAs could theoretically support up to 4 × the total extant population of wild African lions (~ 83, 000), providing a measurable benchmark for future conservation efforts. The performance of PAs shows marked geographic variation, and in several countries there is a need for a significant elevation in conservation effort. Bushmeat poaching was identified as the most serious threat to both lions and to wildlife in general. The severity of threats to wildlife in PAs and the performance of prey populations were best predicted by geographic-socioeconomic variables related to the size of PAs, whether people were settled within PAs, human/livestock densities in neighbouring areas and national economic indicators. However, conservation outcomes for lions were best explained by management variables. PAs tended to be more effective for conserving lions and/or their prey where management budgets were higher, where photographic tourism was the primary land use, and, for prey, where fencing was present. Lions and prey fared less well relative to their estimated potential carrying capacities in poorer countries, where people were settled within PAs and where PAs were used for neither photographic tourism nor trophy hunting.